2011
DOI: 10.1007/s00421-011-2034-9
|View full text |Cite
|
Sign up to set email alerts
|

Effects of exercise intensity and duration on nocturnal heart rate variability and sleep quality

Abstract: Acute physical exercise may affect cardiac autonomic modulation hours or even days during the recovery phase. Although sleep is an essential recovery period, the information on nocturnal autonomic modulation indicated by heart rate variability (HRV) after different exercises is mostly lacking. Therefore, this study investigated the effects of exercise intensity and duration on nocturnal HR, HRV, HR, and HRV-based relaxation, as well as on actigraphic and subjective sleep quality. Fourteen healthy male subjects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
105
2
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 122 publications
(115 citation statements)
references
References 39 publications
7
105
2
1
Order By: Relevance
“…We did not investigate the effects of increased exercise duration on nocturnal HRV, but based on the results during short-term recovery, probably no differences would have been noticed, since differences between exercises were quite small at the end of the 15 min controlled recovery. In contrary, in a recent study by Myllymäki et al (2012), exercise duration was increased from 30 minutes to 90 minutes at the intensity of 60 % vVO2max in moderately physically active male subjects, which is quite similar to exercise protocols of the recreationally trained subjects of the present study. They found increased nocturnal HR after 90 min exercise when compared to 30 or 60 min exercises, and decreased HRV after 90 min exercise when compared to a control day without exercise.…”
Section: The Effects Of Exercise Duration On Post-exercise Hrvsupporting
confidence: 46%
See 1 more Smart Citation
“…We did not investigate the effects of increased exercise duration on nocturnal HRV, but based on the results during short-term recovery, probably no differences would have been noticed, since differences between exercises were quite small at the end of the 15 min controlled recovery. In contrary, in a recent study by Myllymäki et al (2012), exercise duration was increased from 30 minutes to 90 minutes at the intensity of 60 % vVO2max in moderately physically active male subjects, which is quite similar to exercise protocols of the recreationally trained subjects of the present study. They found increased nocturnal HR after 90 min exercise when compared to 30 or 60 min exercises, and decreased HRV after 90 min exercise when compared to a control day without exercise.…”
Section: The Effects Of Exercise Duration On Post-exercise Hrvsupporting
confidence: 46%
“…In previous studies, it has been shown that the effects of a high-intensity prolonged exercise on post-exercise HRV may be observed until the night following exercise or even longer (Hautala et al 2001;Hynynen et al 2010;Mourot et al 2004), either when compared to resting day (Hautala et al 2001) or some kind of control exercise Myllymäki et al 2012). In the study of Hynynen et al (2010), the intensity of the baseline exercise was increased, so the exact effects of the increased duration of exercise cannot be analyzed, but the results of the study indicated a long-lasting decrement of vagal activation after high-intensity endurance exercise.…”
Section: The Effects Of Exercise Duration On Post-exercise Hrvmentioning
confidence: 99%
“…The following HRV parameters elicited from the data were analyzed: standard deviation of normal-to-normal intervals (SDNN), root mean square of successive differences (RMSSD), very low frequency power (VLF) (0.003-0.04 Hz), low frequency power (LFP) (0.04-0.15 Hz), high frequency power (HFP) (0.15-0.40 Hz), low to high frequency ratio (LF/HF), and total power (TP). The same software also computes stress and relaxation percentages for the recording period using the neural network modeling [21], and both of them were used in the later analysis.…”
Section: Statisticsmentioning
confidence: 99%
“…No changes in HRV were found after three months of the aerobic training program. Recently, Myllymäki and colleagues published two papers focusing exclusively on cardiac autonomic function during sleep 36,37) . Their studies were designed to observe the acute effects of single bouts of exercise on later sleep.…”
Section: Effect Of Exercise On Cns Sleepmentioning
confidence: 99%